Persistence and dynamics of fluorescent Lactobacillus plantarum in the healthy versus inflamed gut. (1st January 2021) - Salomé-Desnoulez, S; Poiret, S; Foligné, B; Muharram, G; Peucelle, V; Lafont, F; Daniel, C
ABSTRACT: The gastrointestinal tract is the main ecological niche in which Lactobacillus strains may provide health benefits in mammals. There is currently a need to characterize host-microbe interactions in space and time by tracking these bacteria in vivo . We combined noninvasive whole-body imaging with ex vivo fluorescence confocal microscopy imaging to monitor the impact of intestinal inflammation on the persistence of orally administered Lactobacillus plantarum NCIMB8826 in healthy and inflamed mouse colons. We developed fluorescent L. plantarum strains and demonstrated that mCherry is the best system for in vivo imaging and ex vivo fluorescence confocal microscopy of these bacteria. We also used whole-body imaging to show that this anti-inflammatory, orally administered strain persists for longer and at higher counts in the inflamed colon than in the healthy colon. We confirmed these results by the ex vivo confocal imaging of colons from mice with experimental colitis for 3 days after induction. Moreover, extended orthogonal view projections enabled us to localize individual L. plantarum in sites that differed for healthy versus inflamed guts. In healthy colons, orally administered bacteria were localized in the lumen (in close contact with commensal bacteria) and sometimes in the crypts (albeit very rarely in contact with intestinal cells). The bacteria were observed within and outside the mucus layer. In contrast, L. plantarum bacteria in the inflamed colon were mostly located in the lumen and (in less inflamed areas) within the mucus layer. In more intensely inflamed areas (i.e., where the colon had undergone structural damage), the L. plantarum were in direct contact with damaged epithelial cells. Taken as a whole, our results show that fluorescently labeled L. plantarum can be used to study the persistence of these bacteria in inflamed guts using both noninvasive whole-body imaging and ex vivo fluorescence confocal microscopy.